Performance comparison of resin-infused thermoplastic and thermoset 3D fabric composites under impact loading. (1st January 2021) - Shah, S.Z.H.; Megat-Yusoff, P.S.M.; Karuppanan, S.; Choudhry, R.S.; Ahmad, F.; Sajid, Z.; Gerard, P.; Sharp, K.
Highlights: The fabrication of 3D composite with a thermoplastic and thermoset matrix using a vacuum infusion process. Single and recurring low-velocity impact responses of resin-infused thermoplastic and thermoset 3D composites were investigated. The damage mechanisms of the thermoplastic 3D composite were explored under low-velocity impact and compared with conventional thermoset 3D composite. The effect of resin toughness on the low-velocity impact performance of 3D composites was studied. Damage accumulation in 3D composites under recurring impact was explored. Abstract: In this paper, the impact performance of a novel resin-infused acrylic thermoplastic matrix-based 3D glass fabric composite (3D-FRC) has been evaluated and compared with thermoset based 3D-FRC under single as well as recurring strike low velocity impact (LVI) events. The single impact tests revealed that the thermoplastic-based 3D-FRC exhibits up to 45% reduced damage area and can have up to 20% higher impact load-bearing capacity (peak force). The damage mode characterization showed that damage transition energy required for micro to macro damage transition is 27% higher, and back face damage extension is up to 3 times less for thermoplastic-based 3D-FRC. Meanwhile, the recurring strike impact test highlights that the thermoplastic-based 3D-FRC experiences a 50% less damaged area, better structural integrity, and survived more strikes. The comparison of single and repeated LVI tests have also allowed us to present a design criterion for estimating the safe number of repeated LVI events for a given impact energy. The superior impact resistance of thermoplastic-based 3D-FRC is attributed to their higher interlaminar fracture toughness, a tougher fiber-matrix interface, matrix ductility, and unique failure mechanism of yarn straining, which is not present in thermoset composites. Graphical abstract: Image, graphical abstract